Three-Dimension Grid Plate Effecting in Mandibular Fracture Fixation - , Rafael Santiago de Almeida, Willian Caetano Rodrigues, Marco Túllio Becheleni Ávila Guimarães, Saulo Gabriel Moreira Falci, Shajadi Carlos Pardo Kaba, Eduardo Hochuli Vieira, Élio Hitoshi Shinohara (Archives of Current Research International, 2024)
Introduction: The mandibular angle fractures in the region of the body represent the highest incidence of fractures in mandibles and therefore deserve special attention and care. The use of three-dimensional plates has shown good results in this type of treatment and use has increased every day. Case Report: The authors describe two cases of mandibular fractures treated with grid miniplate. In case 1, was carried out extra-oral access for fracture reduction in angle. In case 2 was also carried out extra-oral access for fracture reduction in mandibular body. The monitoring showed the surgical success and the absence of postoperative complications. The grid miniplate has shown a great treatment option in cases of fractures of the mandibular body and angle for ease of use and lower rates of postoperative complications. Conclusion: The use of a three-dimensional grid plate has proven to be a viable alternative for the osteosynthesis of mandibular fractures. The results have significant clinical implications and encourage its use.